1988
DOI: 10.1063/1.340487
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of the concentration of the carbon-associated radiation damage levels with the total carbon concentration in silicon

Abstract: The dominant carbon-related radiation damage center in silicon was studied in detail by deep level transient spectroscopy. Samples with different carbon and oxygen content were implanted with gradually increasing proton fluence. Two energetically closely spaced levels were revealed and tentative identities were assigned. One at ET+EV=0.344 eV (σp=1.1×10−16 cm2) is assigned as the C+Oi complex, and that at ET+EV=0.370 eV (σp=8×10−18 cm2) is assigned as the Cs-Sii-Cs complex. It was shown that the concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 15 publications
2
24
0
Order By: Relevance
“…4). Comparing with literature data, 14,15,[25][26][27][28][29][30] it is concluded that the hole trap found in the p-type silicon substrate after RTA most likely corresponds with C i O i -related centers, although the σ p is about one decade higher than the typically reported values. This could be due to the effect of the negative feature observed in Fig.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…4). Comparing with literature data, 14,15,[25][26][27][28][29][30] it is concluded that the hole trap found in the p-type silicon substrate after RTA most likely corresponds with C i O i -related centers, although the σ p is about one decade higher than the typically reported values. This could be due to the effect of the negative feature observed in Fig.…”
Section: Discussionmentioning
confidence: 46%
“…The fact that a CZ silicon substrate is used, makes it very likely that C i becomes trapped by O i in the bulk of the wafer. 14,15,[25][26][27][28][29][30] Another potential source of oxygen could be traces of moisture in the RTA annealing ambient, where oxygen diffuses in from the surface. It is also concluded from the DLTS results reported here that during RTA additional carbon atoms are transformed from substitutional into interstitial positions, 31 explaining at least part of the loss of stress after high-temperature annealing.…”
Section: Discussionmentioning
confidence: 99%
“…The formation of dimmers and also their diffusivity is also expected to be enhanced. Thus, larger concentrations of VO 5 and VO 6 defects are produced, making them detectable in the IR spectra. On the other hand, the role of tin on the evolution of carbon-related defects and in par- ticular on the formation of the C s O 2i defect cannot be definite extracted from these measurements.…”
Section: Contributedmentioning
confidence: 98%
“…It is worth noting that the above four weak bands of VO 5 and VO 6 defects appear in the IR spectra of neutron irradiated Cz-Si received at room temperature [8], as well as in the spectra of electron irradiated Si received at He liquid temperatures [9]. Understandingly, in neutron irradiation the concentration of defects is comparably larger than that of electron irradiation, allowing their detection at room temperatures measurements in the former case which may not be detected in the latter case.…”
Section: Contributedmentioning
confidence: 99%
See 1 more Smart Citation